Lahar floods in West Sumatra during the Dutch colonial era: Historical records and societal impact - Narny Yenny; Rahayu Putri Febriani; Cribb Robert; Denny; Pratika Sari Dewi; Siskha Sari Elvia; Anas Ismail Febrin; Anwar Khairil; Aziz Nasta Abdul; Yuliardi Yozi (E3S Web of Conferences)
This research explores documents and archives regarding lahar floods in West Sumatra during the Dutch colonial period. These records are crucial amid difficulties in obtaining historical statistical data to study similar past disasters. The research method used is historical, integrating information from Dutch colonial documents and archives such as newspapers, magazines, diaries (dagh register), government reports, and contemporary books, particularly those discussing societal conditions and Dutch government policies in handling various lahar flood events in West Sumatra during that period. This study is expected to provide new insights for the development of disaster studies and facilitate historical disaster studies in other Indonesian regions that are also prone to natural disasters.